A Developmental Approach to Understanding Gender Differences Among Youth Offenders Regarding Perceptions of Police Legitimacy - Lee, Selye (International criminal justice review, 2024)
While there is a rich body of literature regarding attitudes toward the police, longitudinal empirical research on perceptions of police legitimacy among youth offenders is scant. Using data from Pathways to Desistance, a longitudinal study of 1,354 serious juvenile offenders, the current study builds upon the literature by identifying developmental trajectories of perceptions of police legitimacy among serious young offenders by gender. The study used group-based trajectory modeling, which yielded five trajectory groups for males and four trajectory groups for females. Female youth offenders exhibited slight increases in perceptions of police legitimacy, whereas males showed variations in perceptions of police legitimacy across the seven waves. To examine the probability that predictors belong to certain trajectory groups, the average marginal effects from a multinomial logit regression model were calculated. The findings showed that direct and indirect procedural justice and Black were statistically significant predictors of the probability of police legitimacy trajectories for both males and females. Compared with the male youth offenders, among their female counterparts, legal cynicism, self-reported offense, Hispanic, and age were not associated with the probability of each trajectory group. Given our findings and the strong association between the likelihood of offending and perceptions of the police, we suggest that existing early intervention programs may add a curriculum on prosocial attitudes toward the police. The findings also shed light on the significance of gender in the developmental perspective of police legitimacy perceptions among youth offenders.